Prenatal weight stigma can affect relationship quality and maternal health outcomes - Taniya S. Nagpal; Angela C. Incollingo Rodriguez (BMC, 2024)
Abstract Background Weight stigma is defined as negative misconception and stereotypes associated with weight, and it is commonly experienced during pregnancy. Weight stigma during pregnancy may be sourced from trusted close relationships including family members, partners, and friends. Social support is a necessary psychosocial factor for optimal health and wellbeing throughout pregnancy, and weight stigma sourced from these integral relationships may negatively affect health outcomes. The purpose of this study was to assess the impact of weight stigma from close others on maternal health outcomes. Methods A survey was administered via Qualtrics to pregnant women (≥ 13 weeks, residence within the United States or Canada, ≥ 18 years old, singleton pregnancy). During pregnancy, participants completed questionnaires identifying whether they had experienced weight stigma from a close relationship (i.e., family, partners, or friends), how often, and relationship quality scales for each source. At three months postpartum, they were surveyed about their pregnancy outcomes including gestational diabetes, gestational hypertension, preeclampsia, chronic pain, anxiety/depression. They also completed the Edinburgh Postpartum Depression Scale (EPDS), and a linear regression was performed with frequency of weight stigma. Logistic regressions were performed between frequency of weight stigma and health outcomes. If significant, relationship quality was tested as a potential mediator. Significance was accepted as p < 0.05. Results 463 participants completed both surveys of which 86% had experienced weight stigma from close others. Frequency of weight stigma was significantly associated with chronic pain (β = 0.689, p < 0.001), and anxiety/depression (β = 0.404, p = 0.005). The relationship between frequency of weight stigma in pregnancy and chronic pain was mediated by quality of all relationships. Family relationship quality mediated between frequency of weights stigma and anxiety/depression. Frequency of weight stigma was significantly associated with depression symptom severity measured by the EPDS (β = 0.634, p < 0.001). Conclusion These findings underscore the issue of weight stigma and show that experiencing this from trusted close others is associated with poor health outcomes like chronic pain. Advocacy efforts to mitigate weight stigma in pregnancy and strengthen close relationships to improve maternal health and wellbeing is warranted.